Hematopoietic stem cells undergo a lymphoid to myeloid switch in early stages of emergency granulopoiesis - Vanickova, Karolina; Milosevic, Mirko; Ribeiro Bas, Irina; Burocziova, Monika; Yokota, Asumi; Danek, Petr; Grusanovic, Srdjan; Chiliński, Mateusz; Plewczynski, Dariusz; Rohlena, Jakub; Hirai, Hideyo; Rohlenova, Katerina; et al. (The EMBO journal, 2023)
Emergency granulopoiesis is the enhanced and accelerated production of granulocytes that occurs during acute infection. The contribution of hematopoietic stem cells (HSCs) to this process was reported; however, how HSCs participate in emergency granulopoiesis remains elusive. Here, using a mouse model of emergency granulopoiesis we observe transcriptional changes in HSCs as early as 4 h after lipopolysaccharide (LPS) administration. We observe that the HSC identity is changed towards a myeloid-biased HSC and show that CD201 is enriched in lymphoid-biased HSCs. While CD201 expression under steady-state conditions reveals a lymphoid bias, under emergency granulopoiesis loss of CD201 marks the lymphoid-to-myeloid transcriptional switch. Mechanistically, we determine that lymphoid-biased CD201+ HSCs act as a first response during emergency granulopoiesis due to direct sensing of LPS by TLR4 and downstream activation of NF-κΒ signaling. The myeloid-biased CD201- HSC population responds indirectly during an acute infection by sensing G-CSF, increasing STAT3 phosphorylation, and upregulating LAP/LAP* C/EBPβ isoforms. In conclusion, HSC subpopulations support early phases of emergency granulopoiesis due to their transcriptional rewiring from a lymphoid-biased to myeloid-biased population and thus establishing alternative paths to supply elevated numbers of granulocytes.
Keywords: Hematopoiesis; emergency granulopoiesis; CD201; Lipopolysaccharides; hematopoéza; Hematopoietic Stem Cells; myeloid-biased HSC; lymphoid-biased HSC; granulocyty; hematopoetické kmenové buňky; lipopolysacharidy; Granulocytes